Directed crystallization of a poly(3,4-ethylenedioxythiophene) film by an iron(III) dodecyl sulfate lamellar superstructure - Feng Ma; Sang-il Choi; Dooyong Lee; Sung Bae Jeon; Sungkyun Park; Sung-Pyo Cho; Jin-Hyo Boo; Sungsoo Kim (Nature Communications, 2024)
Abstract Poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), a successfully commercialized polymeric semiconductor material, has potential as a transparent electrode in flexible electronic devices, yet has insufficient conductivity. We present the synthesis, properties, and directed crystallization of the PEDOT:dodecyl sulfate (PEDOT:DS) film. Iron(III) dodecyl sulfate (Fe(DS)3) multi-lamellar vesicles (MLVs), a new growth template, are used to synthesize and direct the growth of the PEDOT:DS film via vapor-phase polymerization of 3,4-ethylenedioxythiophene to form huge PEDOT:DS co-crystal domains within the MLV superstructure. The polycrystalline film has metallic conductivity (avg. ~1.0 × 104 S cm−1), is highly transparent and mechanically durable yet flexible, and suitable for next-generation flexible electronics. These noteworthy properties are conferred by the MLV lamellar superstructure of Fe(DS)3, a selective oxidant and an efficient in situ dopant that enhances the film hydrophobicity and durability. Sophisticated MLV-type oxidants are foreseen to enable the synthesis of more conductive, transparent, robust, flexible, and water-stable polymer electrode materials in future.